Enjoying Sad Music: Paradox or Parallel Processes? - Schubert, Emery (Frontiers in Human Neuroscience, 2016)
Enjoyment of negative emotions in music is seen by many as a paradox. This article argues that the paradox exists because it is difficult to view the process that generates enjoyment as being part of the same system that also generates the subjective negative feeling. Compensation theories explain the paradox as the compensation of a negative emotion by the concomitant presence of one or more positive emotions. But compensation brings us no closer to explaining the paradox because it does not explain how experiencing sadness itself is enjoyed. The solution proposed is that an emotion is determined by three critical processes—labeled motivational action tendency (MAT), subjective feeling (SF) and Appraisal. For many emotions the MAT and SF processes are coupled in valence. For example, happiness has positive MAT and positive SF, annoyance has negative MAT and negative SF. However, it is argued that in an aesthetic context, such as listening to music, emotion processes can become decoupled. The decoupling is controlled by the Appraisal process, which can assess if the context of the sadness is real-life (where coupling occurs) or aesthetic (where decoupling can occur). In an aesthetic context sadness retains its negative SF but the aversive, negative MAT is inhibited, leaving sadness to still be experienced as a negative valanced emotion, while contributing to the overall positive MAT. Individual differences, mood and previous experiences mediate the degree to which the aversive aspects of MAT are inhibited according to this Parallel Processing Hypothesis (PPH). The reason for hesitancy in considering or testing PPH, as well as the preponderance of research on sadness at the exclusion of other negative emotions, are discussed.